The Lion, the witch and the wardrobe - Lewis, C.L. (Hong Kong : Collins, 1996)
Four English schoolchildren find their way through the back of wardrobe into the magic land of Narnia and assist Aslan, the golden lion, to triumph over the White Witch, who has cursed the land with enternal winter.
Keywords: Fantasy